Analysis of Motivation, Leadership Style, and Communication on the Performance of Members of the Sulawesi Truck Driver Association Kotamobagu Branch through Job Satisfaction As an Intervening Variable - Dotulong, Lucky; Loindong, Sjendry; Sumarauw, Jacky; Lintong, Debry Ch. A. (International Journal of Artificial Intelligence Research, 2023)
The background of this research is that the performance of members of the Sulawesi Truck Driver Association, Kotamobagu City branch, has not been maximized. There are still accidents on the road or when loading and unloading goods and complaints from transportation users who use the services of members of the Sulawesi Truck Driver Association, Kotamobagu City branch personally which makes losses in terms of material service users. Such performance results in the organization's name becoming bad. The purpose of this study was to analyze motivation, leadership style, and communication on the performance of members of the kotamobagu branch of the sulawesi truck driver union through job satisfaction as an intervening variable. The research stages carried out were field observations, then literature studies, data collection both primary and secondary. Followed by research, data analysis and discussion, after that draw conclusions and provide suggestions. The results showed that the variables of motivation, leadership style, and communication had no effect on the job satisfaction of truck drivers who were members of the Sulawesi truck driver union, Kotamobagu city branch. motivation, leadership style, communication, and job satisfaction have no effect on the performance of truck drivers who are members of the Sulawesi truck driver union, Kotamobagu city branch.